Study of Water Quality Index for Assessment of Characteristics of Water of Budhi Gandak River Near Muzaffarpur District of Bihar - Diksha Joshi; Dr. Faiyaj Ahmad (International Journal of Scientific Research in Science and Technology, 2024)
This paper presents the environmental quality is greatly focused on water because of its importance in maintaining human health and the health of the ecosystem. The Water Quality Index (WQI) is an arithmetic tool used to transform large water quality data into a single number that represents the water quality level for human consumption. In the present study surface water samples in summer, monsoon, and winter seasons were collected at three sampling sites in the Budhi Gandak River near Muzaffarpur for assessment of river water quality. The water quality variables analyzed for assessment of river water quality included temperature, pH, turbidity, total dissolved solids (TDS), conductivity, total hardness (TH), dissolved oxygen (DO), total alkalinity (TA), phosphate (PO¯), nitrate (NO¯) and chloride (Cl¯). The results indicated that most of the physico-chemical parameters were within the WHO limits (1998) and BIS: 10500(2004-2005) for drinking water except turbidity values which exceeded (18.55- 58.37 NTU) the maximum permissible limit of Indian standards at all the three sites in all the three seasons The seasonal water quality data showed the pH in the range of 6.9-7.3, DO in the range of 4.9-8.71 mg/L and total hardness in the range of 187.5-246.0 mg/L. A water quality index was calculated considering the relative weights of 9 water quality parameters following the calculation method prescribed by Ramakrishnaiah et al., 2009 and Gebrehiwot et al., 2011. WQI was in the range of good category (63.45-87.35) in the summer and winter seasons at each site and in the range of poor category in the monsoon season almost at all three sites.
Keywords: River Budhi Gandak; Water Quality; WQI